Radiomic features of amygdala nuclei and hippocampus subfields help to predict subthalamic deep brain stimulation motor outcomes for Parkinson‘s disease patients - Saudargiene, Ausra; Radziunas, Andrius; Dainauskas, Justinas J.; Kucinskas, Vytautas; Vaitkiene, Paulina; Pranckeviciene, Aiste; Laucius, Ovidijus; Tamasauskas, Arimantas; Deltuva, Vytenis (Frontiers in Neuroscience, 2022)
Background and purpose: The aim of the study is to predict the subthalamic nucleus (STN) deep brain stimulation (DBS) outcomes for Parkinson’s disease (PD) patients using the radiomic features extracted from pre-operative magnetic resonance images (MRI). Methods: The study included 34 PD patients who underwent DBS implantation in the STN. Five patients (15 %) showed poor DBS motor outcome. All together 9 amygdalar nuclei and 12 hippocampus subfields were segmented using Freesurfer 7.0 pipeline from pre-operative MRI images. Results: Furthermore, PyRadiomics platform was used to extract 120 radiomic features for each nuclei and subfield resulting in 5040 features. Minimum Redundancy Maximum Relevance (mRMR) feature selection method was employed to reduce the number of features to 20, and 8 machine learning methods (regularized binary logistic regression, decision tree classifier, linear discriminant analysis, naive Bayes classifier, kernel support vector machine, deep feed-forward neural network, one-class support vector machine, feed-forward neural network-based autoencoder for anomaly detection) were applied to build the models for poor vs good and very good STN-DBS motor outcome prediction. The highest mean prediction accuracy was obtained using regularized logistic regression (96.65 ± 7.24 %, AUC 0.98 ± 0.06) and deep feed-forward neural network (87.25 ± 14.80 %, AUC 0.87 ± 0.18). Conclusion: The results show the potential power of the radiomic features extracted from hippocampus and amygdala MRI in the prediction of STN-DBS motor outcomes for PD patients.